2021
DOI: 10.3390/ijms22115853
|View full text |Cite
|
Sign up to set email alerts
|

The Potential of Asiatic Acid in the Reversion of Cyclophosphamide-Induced Hemorrhagic Cystitis in Rats

Abstract: The purpose of this study was to determine if asiatic acid may act efficiently in the model of cyclophosphamide (CYP)-induced cystitis in rats. We performed experiments after administration of CYP (single dose 200 mg/kg, intraperitoneally), asiatic acid (30 mg/kg/day for 14 consecutive days, by oral gavage), or CYP plus asiatic acid, during which conscious cystometry, measurements of urothelium thickness and bladder edema, as well as selected biomarkers analyses were conducted. In rats that received asiatic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
2

Year Published

2021
2021
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
(79 reference statements)
1
14
0
2
Order By: Relevance
“…We did not observe any synergism of mesna and carvedilol, but the mean bladder index was the lowest in both groups receiving mesna and significantly lower not only in the CPX group, but also in the CPX-C group. As expected, CPX caused a significant increase in bladder MDA level, which is consistent with other studies [9,51]. What is surprising is that, despite many reports about the antioxidant activity of carvedilol in, e.g., doxorubicin-induced cardiotoxicity [25] or in mice model of diabetes [62], we did not observe a decrease in bladder MDA concentration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We did not observe any synergism of mesna and carvedilol, but the mean bladder index was the lowest in both groups receiving mesna and significantly lower not only in the CPX group, but also in the CPX-C group. As expected, CPX caused a significant increase in bladder MDA level, which is consistent with other studies [9,51]. What is surprising is that, despite many reports about the antioxidant activity of carvedilol in, e.g., doxorubicin-induced cardiotoxicity [25] or in mice model of diabetes [62], we did not observe a decrease in bladder MDA concentration.…”
Section: Discussionsupporting
confidence: 91%
“…Additionally, the generation of reactive oxygen species (ROS), overexpression of cyclooxygenase-2 (COX-2) and inducible nitric oxide synthase (iNOS), involvement of bradykinin, substance P, and platelet-activating factor (PAF) is important or suggested in this pathological pathway. This leads to the destruction of the urothelium, erosions, ulcerations, pain, and bladder overactivity with the possible role of activation of alpha-1 adrenergic receptors [6][7][8][9]. In addition to the well-described toxicity of CPX in urinary bladders, kidneys are also often affected.…”
Section: Introductionmentioning
confidence: 99%
“…The role of several cytokines in pathogenesis of CYP-induced HC were described 29 . IL-1β is a pivotal cytokine that triggers the immune response and stimulates the pro-inflammatory response (via TNF α and IL-6) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Cystometry is an effective method to assess bladder function. Previous studies have found that bladder compliance decreases and urination frequency increases after CYP treatment [ 26 ]. Similarly, bladder neuropathy caused by diabetes has been shown to increase the maximum bladder capacity and residual urine volume.…”
Section: Discussionmentioning
confidence: 99%